Intercollegiate athletics and the American university : a university president's perspective - Duderstadt, James J., 1942- (University of Michigan Press, 2000)
"At the University of Michigan and elsewhere, big-time college football and basketball have become largely independent, commercial enterprises. Although there is some general consensus that big-time college sports can seriously damage a university and its students, not only because of the occasional scandal and corruption but, more seriously, because of the underlying culture of commercialism and hypocrisy, efforts over the years to reform and deemphasize college football and basketball have been largely ineffective. This issue has special urgency now, as higher education enters an era of profound change. Today the viability and importance of the university as a social institution is being called into question as universities struggle to respond to the needs of a knowledge-driven society